Poetry and Emphatic Truth: Walter Benjamin’s Reading of Hölderlin - Eldridge, Richard (Analysis. Journal of Philosophical Research, 2015)
Resumen El presente trabajo comenta la teoría poética de Walter Benjamin. Se hace notar que Benjamin sigue a Hölderlin al considerar que un verdadero poema es una configuración particular en la que se juntan los órdenes intelectual y perceptivo. Un verdadero poema aspiraría no a la verdad como correspondencia con un objeto determinado, sino a algo que en el texto se describe como “verdad enfática”. Palabras clave: Walter Benjamin, Hölderlin, verdad empática, crítica literaria Abstract Benjamin’s poetic theory is commented. It is noted that Benjamin follows Hölderlin in regarding a successful poem as a particular configuration that joins the intellectual and perceptual orders. Such a successful poem aims at and can possess not truth as correspondence to a given object, but rather what in the text is described as “emphatic truth”. Keywords: Walter Benjamin, Hölderlin, emphatic truth, literary criticism